Legal Dimensions of International Framework Agreements in the Field of Corporate Social Responsibility - Sobczak, André (Relations industrielles / Industrial Relations, 2007)
The aim of this article is to offer an in-depth analysis of the different legal aspects of international framework agreements (IFAs) negotiated between multinational companies and global union federations. Using examples from different agreements, the article shows the potential added value IFAs have in contributing to an effective social regulation within international groups and global supply chains that are today regulated insufficiently by national, European and international labour law standards. It also analyses the impact of the international negotiation process of the IFAs and the powers of the signatory parties on the legally binding character of these texts. To conclude, the article discusses the potential added value of an optional legal framework for IFAs.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; International law; Labor Unions; Labor law; Labor negotiations; Multinational corporations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social responsibility

La responsabilité sociale de l’entreprise : Menace ou opportunité pour le droit du travail ? - Sobczak, André (Relations industrielles / Industrial Relations, 2004)
Largement dominant à l’époque de la production industrielle dans l’entreprise hiérarchisée, le contrat de travail à durée indéterminée comme mode de régulation des relations de travail est aujourd’hui doublement fragilisé par l’organisation des entreprises sous forme de réseaux et par le recours à des outils de la responsabilité sociale de l’entreprise qui visent à réguler les relations de travail dans ces réseaux. L’objectif de cet article est d’analyser les enjeux de l’émergence de cette nouvelle forme de régulation pour le droit du travail. Le recours aux instruments de la responsabilité sociale renforce-t-il la crise du droit du travail ou, au contraire, permet-il de l’atténuer ? En d’autres termes, faut-il considérer que la responsabilité sociale concurrence les normes du droit du travail, ou peut-elle utilement les compléter, voire même leur donner une opportunité de renouvellement dans le contexte difficile des entreprises en réseaux ?